Cross-cultural challenges to Expatriates in Finland - Uddin , Waqar (My University, 2011)
Organizations open their subsidiaries in different countries, for this purpose they send their employees overseas as expatriates for effective management and control of their business. Effective performance of expatriates is recognized as a major determinant in the success or failure of organisations but these expatriates face many challenges due to different culture and environment during their cross-cultural adjustment. The purpose of this exploratory, qualitative study was to determine the challenges facing Indian expatriates who are working in Finland and to determine what Factors are affecting their cross-cultural adjustment and job adjustment. Data was obtained through semi- structured interviews and short questioners to seven (7) Indian expatriates working in MNCs in Finland. The empirical Study shows that not a single factor which determines expatriate cross-cultural adjustment. There are many other factors such as adjustment of their family and spouse, Host country Languages skill, Personal qualities, organizational support, job factors and non-work factors affects expatriate cross-cultural adjustment in new environment. This study gives an idea about the improvement of expatriation process and further suggestions to companies to adopts and develop such measures which facilitates expatriates cross-cultural and job adjustment.
Keywords: KEY WORDS: Expatriates; Cross-Cultural Adjustment; Job Adjustment; Cultural shock; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in International Business|